2008
DOI: 10.1051/apido:2008036
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic correlations of field and laboratory tests with honey production in Africanized honey bees (Apis mellifera)

Abstract: Africanized honey bees (Apis mellifera; AHB) are predominant in tropical Mexico. A selection program using local AHBs colonies is a good alternative to provide beekeepers with good quality queens. We evaluated the application of field and laboratory tests to predict the production of honey in AHBs from Yucatan, Mexico. Five variables were measured in worker bees in the laboratory: longevity, amount of syrup removed, hoarding, weight of pupae and corbicular area. Three additional variables were measured in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Certain studies in the literature have shown a positive phenotypic correlation between the amounts of syrup gathered or collected by bees (hoarding behavior) in the laboratory/field and the honey production in the hives (Olszewski and Paleolog, 2005; Zárate et al , 2008). Another study also found a positive correlation (Pearson) between PP and HP in Africanized honeybees, with r = 0.422 (p = 0.00001256), showing that the bees that produced more propolis also produced more honey (Manrique and Soares, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Certain studies in the literature have shown a positive phenotypic correlation between the amounts of syrup gathered or collected by bees (hoarding behavior) in the laboratory/field and the honey production in the hives (Olszewski and Paleolog, 2005; Zárate et al , 2008). Another study also found a positive correlation (Pearson) between PP and HP in Africanized honeybees, with r = 0.422 (p = 0.00001256), showing that the bees that produced more propolis also produced more honey (Manrique and Soares, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…; Pereira & Chaud‐Netto ; Zárate et al . ; Livanis & Moss ). These factors, but particularly their heightened defensiveness (Collins et al .…”
Section: Introductionmentioning
confidence: 99%
“…Pupal weight, corbicular size, and proboscis length have been correlated honey production in temperate honey bees (Milne Jr. 1980;Milne Jr. and Pries 1984). In AHBs, honey production is also influenced by pupal weight (Souza et al 2002;Zárate et al 2008) and significantly correlated with the corbicular area (Souza et al 2002). Indeed, smaller bees may have limited capacity to carry large or heavy loads (Milne Jr. and Pries 1986), reducing the opportunity of colonies to accumulate large reserves which in turn may compromise colony reproduction and survival, as well as productivity.…”
Section: Discussionmentioning
confidence: 99%